1997
DOI: 10.1126/science.277.5328.933
|View full text |Cite
|
Sign up to set email alerts
|

The World's Smallest Gas Cylinders?

Abstract: Rev. Sci. Instrum. 50, 1002 (1979] were used with either Re or spring-steel gaskets to compress the samples, which consisted of cryogenically loaded Xe along with Fe powder (<20 |xm grain size) and less than 10 volume % fine-grained ruby (<5 |xm grain size); the latter is used for pressure calibration [H. K. Mao, P. M. Bell, J. W. Shaner, J. Steinberg, J. Appl. Phys. 49, 3276 (1978)]. Samples were heated inside the diamond cell by means of a Quantronix 117 continuous-wave Nd:YAG laser operated in the TEM00 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(90 citation statements)
references
References 25 publications
1
87
0
2
Order By: Relevance
“…[49][50][51][52][53][54][55][56] In the last few years significant efforts have been directed towards optimization of the process condition for CF formation. Researchers have investigated CF formation on different metal-based catalysts.…”
Section: Production Of Carbon Filaments By Catalytic Methane Decomposmentioning
confidence: 99%
“…[49][50][51][52][53][54][55][56] In the last few years significant efforts have been directed towards optimization of the process condition for CF formation. Researchers have investigated CF formation on different metal-based catalysts.…”
Section: Production Of Carbon Filaments By Catalytic Methane Decomposmentioning
confidence: 99%
“…However, the major issues pertaining to these techniques are related to the fact that CNTs are not able to encapsulate gaseous substances. Recent studies have revealed that H 2 and Ar can be stored in SWNTs [125,126] and MWNTs [127], respectively. Terrones et al [128] demonstrated experimentally that it is possible to introduce gaseous nitrogen inside MWNTs using a single-step process.…”
Section: Gas and Hydrogen Storagementioning
confidence: 99%
“…The hollow part of the structure, inside the CNTs, could be considered as a confinement space where certain compounds can enter [4]. Therefore, there are interesting possible applications for open-ended CNTs, such as gas adsorbents [5,6], using them as molds to form one dimensional (quantum) systems [7,8], place catalysts on them [9], or use them as molecular filters for water treatment [10]. Hence, the adsorption and diffusion of chemical species (like water, gases etc.)…”
Section: Introductionmentioning
confidence: 99%